Using and developing measurement instruments in science education : a Rasch modeling approach - Liu, Xiufeng, 1962- (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"This book meets a demand in the science education community for a comprehensive and introductory measurement book in science education. It describes measurement instruments reported in refereed science education research journals, and introduces the Rasch modeling approach to developing measurement instruments in common science assessment domains, i.e. conceptual understanding, affective variables, science inquiry, learning progression, and learning environments. This book can help readers develop a sound understanding of measurement theories and approaches, particularly Rasch modeling, to using and developing measurement instruments for science education research. This book is for anyone who is interested in knowing what measurement instruments are available and how to develop measurement instruments for science education research. For example, this book can be a textbook for a graduate course in science education research methods; it helps graduate students develop competence in using and developing standardized measurement instruments for science education research. Science education researchers, both beginning and experienced, may use this book as a reference for locating available and developing new measurement instruments when conducting a research study"-- Provided by publisher.
Keywords: Science -- Study and teaching.; Educational tests and measurements.; Rasch models.; Education -- Teaching -- Subjects -- Science & Technology.; Teaching of a specific subject.; Educational: Sciences, general science.; elektronické knihy; electronic books